Քաղաքական երկխոսութային հաղորդակցման առանձնահատկությունները - Գալստյան, Խաչիկ (YSU Journal of International Affairs, 2015)
Within the framework of this article, the author examines the basic models of political communications, identifies the characteristics and functional features of the application of dialogue forms of communication in the political space of modern society. In particular, highlighting the basic principles of building dialogue relationships in the communication field, the author offers an original - a dialogue oriented model of political PR Communications (DOPR), as the most effective mechanism to prevent political conflicts and building long-term PR communications in the political system of modern society.
Keywords: dialogue communication, linear communication, nonlinear communication, dialogue-oriented PR communications